The Genius of John Paul II: The Great Pope's Moral Wisdom - Spinello, Richard A. (Rowman & Littlefield Publishers, 2006)
In this exciting new book, renowned ethicist Richard Spinello offers the first comprehensive presentation of the late John Paul II's great moral vision. Here admirers may read and understand the essential teachings of the pope in his own words as Spinello draws on his extensive research into John Paul II's writings and talks. Subjects covered include reverence for life, concern for the poor and suffering, moral law, conscience, moral choice, intrinsically evil acts, freedom, and goodness. The purpose of this book is two-fold: it not only persuasively presents the late pope's vital teachings, but also defends them against his critics. This important new work preserves and promotes the extraordinary legacy of John Paul II by focusing on his championing of universal human dignity and objective moral truths.